Factors influencing the target costing process - Savickas, Vilius; Šarupičiūtė, Julija (Buhalterinės apskaitos teorija ir praktika, 2014)
The article presents principles of defining target price, target profit and target cost and conjoint concept of target costing process. Functions, performed by employees and departments of an organization during the target costing process are defined. The main direct and indirect factors influencing the determination of target cost and target costing process are proposed. Based on the analysis of literature it is stated, that organizational functions that play an important role in the process of target costing are strategic management, marketing, engineering and manufacturing and cost planning and accounting. The level of influence of target costing related factors can differ, however to achieve cost reducing goals organization should pay attention to customer preferences, supplier abilities, the negative influence of competitors, technological production experience and previous profitability.